Human mitochondrial leucyl tRNA synthetase can suppress non cognate pathogenic mt‐tRNA mutations. Issue 2 (10th January 2014) - Hornig‐Do, Hue Tran; Montanari, Arianna; Rozanska, Agata; Tuppen, Helen A; Almalki, Abdulraheem A; Abg‐Kamaludin, Dyg P; Frontali, Laura; Francisci, Silvia; Lightowlers, Robert N; Chrzanowska‐Lightowlers, Zofia M
Synopsis <boxed-text content-type="graphic" id="emmm201303202-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> A non‐cognate mitochondrial aminoacyl tRNA synthetase can overcome the respiratory defect caused by an mt‐tRNA mutation. The pathogenic mutation can be suppressed by a short peptide corresponding to the C‐terminus of leucyl tRNA synthetase. Human mitochondrial leucyl tRNA synthetase (LARS2) can bind many species of mt‐tRNAs, not exclusively mt‐tRNAleu(UUR) or mt‐tRNAleu(CUN) Binding can stabilize mt‐tRNAs that carry pathogenic destabilizing mutations such as that generated from the m.1624C>T in the gene encoding mt‐tRNAVal A C‐terminal peptide of LARS2 is able to access the mitochondrial matrix and bind a similar spectrum of mt‐tRNAs to the complete LARS2 protein This short peptide has potential to be a therapeutic molecule for many pathogenic mt‐tRNA mutations.